Cruel and Usual - Mary Lourdes Silva; Josephine Walwema; Matt Thomas (Journal of the Scholarship of Teaching and Learning, 2025)
In higher education, student evaluation of teaching (SET) has been under scrutiny for its lack of validity, weak correlation with student learning, and bias toward historically marginalized faculty. Absent from the literature are the psychological and financial implications of negative SETs. In an exploratory mixed methods study of 344 instructors, our findings reveal that the majority of respondents have been impacted both psychologically and financially. Female faculty and faculty of color are disproportionately affected psychologically with female faculty reporting negative affective experiences for 5 to 20+ years. Common reasons include feelings of powerlessness, frustrations with SETs as a metric for teacher quality, and biases linked to instructors' identities. Financially, both female faculty and faculty of color were more likely to report measurable and immeasurable financial losses, ranging from denial of promotion to additional time for student care or decreased time to advance one’s career. The pressure on historically marginalized faculty to counter bias in SETs has wide-ranging psychological and financial repercussions, which underscores the labor inequities of an unjust system of assessment and the ethical implications of universities and colleges requiring faculty to review biased, and at times, abusive student comments.